THERMAL EFFICIENCY ANALYSIS ON THE STEAM POWER PLANT IN NII TANASA BY USING A TWO-SEMESTER DIRECT METHOD WITH A CAPACITY OF 2 x 10 MW - Hasanudin, La; Saefuddin, Laode; Lolok, Agustinus; Balaka, Ridway; Adnal, Adnal; Imran, Al Ichlas; Kadir, Kadir; Kadir, Abd; Aminur, Aminur (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2019)
The thermal efficiency of a steam power plant is very important to know because it involves the initial input of a steam supply that will turn a turbine. This is done to analyze how much thermal efficiency is used in the generation system, so that it can be seen the continued use of the generation system, which is influenced by the value of the Net Plant Heat rate (NPHR). The purpose of this study is to analyze the thermal efficiency of the steam power plant. The method used is the direct method, using a two-semester system namely: semester one (January-June) and then taking months that represent or tend to be stable data, as well as the second semester (July-December). Analysis results In the case study of a steam power plant in Nii Tanasa, the average thermal efficiency value was 17.09%, while in the second semester the analysis of thermal efficiency values was obtained an average value of 15.54%. This value still tends to be low at a capacity of 100 MW, so it is necessary to evaluate the value of the Net plant heat rate (NPHR), especially the type of fuel used, because the calculation on thermal efficiency is strongly influenced by that value.Â Key words: NPHR, Efficiency, Semester, steam, thermal